Understanding forests-people links: the voice of social scientists - Colfer, C.J.P.; Dounias, E.; Goloubinoff, M.; López, C.; Sunderlin, William D. (CAB International, 2006)
This chapter uses an historical case study approach to convey some sense of the kinds of research social scientists do at the Center for International Forestry Research (CIFOR). It describes CIFOR's work in developing criteria and indicators for sustainable forest management, which led to the creation of the programme entitled 'Local People, Devolution, and Adaptive Collaborative Management of Forests'. The experience of two other CIFOR programmes are discussed: 'Underlying Causes of Deforestation' (UCD) and 'Forest Products and People' (FPP, previously 'Nontimber Forest Products'). UCD focuses on policy issues, with a nearly exclusive socioeconomic orientation. FPP's central orientation is on economic and, to a lesser extent, ecological concerns, but it too includes a considerable amount of social science. The chapter ends with a discussion on some organizational aspects of CIFOR.